Membumikan Adab: Menyingkap Gagasan Al-Attas sebagai Fondasi Pendidikan Karakter Generasi Z - Nabila, Mutiara; Manasikana, Arina; Mumtaza, Ukhty; Sari, Herlini Puspika (LPPM UM Metro, 2025)
This study aims to analyze and implement the concept of adab (etiquette) proposed by Syed Muhammad Naquib Al-Attas as a philosophical foundation in addressing the crisis of character education and moral erosion among Generation Z in the digital age. Generation Z, who live in a digital and global environment, experience value disorientation due to the weak internalization of adab in an education system that tends to be cognitive and materialistic. Through a literature review using a qualitative-descriptive analytical approach, this study examines Al-Attas' major works, particularly The Concept of Education in Islam, as well as various literature related to the character crisis and the dynamics of Generation Z. The results of the analysis show that, according to Al-Attas, manners are not merely social etiquette, but rather a spiritual and intellectual awareness to place everything in its proper position according to its essence. The concept of Islamization of Knowledge (IIEP) becomes an implementative instrument for the formation of civilized human beings (al-insan al-mu'addab) through the purification of knowledge from secular values towards a monotheistic orientation. This study concludes that effective character education for Generation Z must be holistic—integrating spiritual, moral, intellectual, and technological aspects to produce a generation that is knowledgeable, moral, and civilized in accordance with the Islamic worldview.